CFD analysis of Pd-Ag membrane reactor performance during ethylbenzene dehydrogenation process. (12th April 2018) - Ghasemzadeh, K.; Zeynali, R.; Bahadori, F.; Basile, A.
Abstract: In this study, the catalytic dehydrogenation of ethylbenzene (EB) to styrene production was investigated in a tubular Pd-Ag membrane reactor (MR) in presence of a commercial iron oxide catalyst. To this purpose, a 2D-axisymmetric, isothermal model based on computational fluid dynamic (CFD) method is presented to investigate the Pd-Ag MR performance during EB dehydrogenation process for styrene and hydrogen production. The proposed CFD model provides the local information of velocity, pressure and component concentration for the driving force analysis. After investigation of mesh independency of CFD model, the validation of model results was carried out by experimental data and a good agreement between model results and experimental data was achieved. It was found that the efficient removal of hydrogen in the Pd-Ag MR could significantly increase the EB conversion. Moreover, using CFD simulation runs, effects of operating parameters such as reaction temperature, pressure and gas hour space velocity (GHSV) values on the Pd-Ag MR performance with two various flow patterns was evaluated in terms of EB conversion and COx -free hydrogen recovery. It can be concluded that the EB conversion realized in Pd-Ag MR with countercurrent flow is higher than the ones achieved for Pd-Ag MR with cocurrent flow and also for traditional reactor (TR) during EB dehydrogenation reaction, in all the studied cases. In particular, under the optimal reaction conditions, 40% enhancement in EB conversion can be obtained in the Pd-Ag MR with countercurrent flow with respect to TR. Graphical abstract: Image 1 Highlights: The ethylbenzene dehydrogenation was modeled in the Pd-Ag MR. The Pd-Ag MR performance was investigated by varying the operating parameters. The CFD analysis was applied for evaluation of concentration, velocity and pressure distribution.